The effect of HIV-1 Vif polymorphisms on A3G anti-viral activity in an in vivo mouse model. Issue 1 (December 2016) - Cadena, Cristhian; Stavrou, Spyridon; Manzoni, Tomaz; Iyer, Shilpa; Bibollet-Ruche, Frederic; Zhang, Weiyu; Hahn, Beatrice; Browne, Edward; Ross, Susan
Abstract Humans encode sevenAPOBEC3 proteins (A–H), with A3G, 3F and 3H as the major factors restricting HIV-1 replication. HIV-1, however, encodes Vif, which counteracts A3 proteins by chaperoning them to the proteasome where they are degraded. Vif polymorphisms found in HIV-1s isolated from infected patients have varying anti-A3G potency when assayed in vitro, but there are few studies demonstrating this in in vivo models. Here, we created Friend murine leukemia viruses encodingvif alleles that were previously shown to differentially neutralize A3G in cell culture or that were originally found in primary HIV-1 isolates. Infection of transgenic mice expressing different levels of human A3G showed that these naturally occurring Vif variants differed in their ability to counteract A3G during in vivo infection, although the effects on viral replication were not identical to those seen in cultured cells. We also found that the polymorphic Vifs that attenuated viral replication reverted to wild type only in A3G transgenic mice. Finally, we found that the level of A3G-mediated deamination was inversely correlated with the level of viral replication. This animal model should be useful for studying the functional significance of naturally occurringvif polymorphisms, as well as viral evolution in the presence of A3G.